Invasive candidiasis among high prevalence neurological patients - Weny Rinawati; July Kumalawati; Saptawati Bardosono; Suzanna Immanuel; Ninik Sukartini; Nuri Dyah Indrasari (Journal of Infection in Developing Countries)
Introduction: Invasive candidiasis is a severe form of infection. The incidence of invasive fungal infections has increased, due to the increasing number of patients with impaired immunity who are being treated through prolonged stay in hospital facilities. Neurological patient treatment methods such as antimicrobials, corticosteroid, central venous catheter (CVC), total parenteral nutrition, and mechanical ventilation use are associated with common risk factors for invasive candidiasis. Our study demonstrated invasive candidiasis prevalence among neurological patients.